Images and ideology. A symptomatic relationship - Lull Sanz, Júlia (Escritura e Imagen, 2025)
Ideology is not only a discourse that separates us from the world, but also alludes to the imaginary representation we make of our real conditions of existence. With this, images become a fertile field for the study of the mechanisms and devices of subjectivation and social control. This text recovers Althusser’s theory of ideology and delves into the role of images in the construction of subjects and subjectivities, while exploring their operational specificity. This proposal considers art history a privileged area for critical knowledge
Keywords: ideology; images; symptom; gender; Althusser